Analisis Resolusi Spasial Citra Ultrasonografi (USG) pada Arah Tangensial Radias Citra menggunakan Phantom Berbasis Silicon Rubber: Victory Immanuel Ratar, Surya Suryasatriya Trihandaru, Giner Maslebu - Victory Immanuel Ratar Victory Immanuel Ratar; Surya Suryasatriya Trihandaru Surya Suryasatriya Trihandaru; Giner Maslebu Giner Maslebu (Jurnal Fisika dan Aplikasinya, 2020)
Ultrasound is widely used in diagnostic imaging, therefore quality control(QC) of ultrasound images is important. One of the QC parameter is spatial resolution that can be analyzed by calculating the distance between two nearby object in the tangential direction of radiation. The image that is produced by the Curved Array transducer will produce a circular shaped image and the coordinates of the object isn’t in the cartesian coordinate system because it adapts to the surface of the transducer. The image must be transformed with a circle equation approach to calculate the distance between two nearby object. This study was using a Mindray 3D ultrasound model: DP-10 with Transducer model: 35C50EB, and phantom instruments made from a mixture of 99 ml silicon rubber and 1 ml catalyst. The acquisition data used a fixed frequency of 4.5 MHz with a gain variation of 168 dB, 182 dB, 202 dB and a depth variation of 3.3 cm, 4.9 cm, 5.7 cm. The result found that the measurement of objects in A area had an error of 0.8963%(0.087 mm),B area was 1.2979%(0.0779 mm), and C area was 2.6296%( 0.1183 mm). The values obtained still meet the standards set by American Association of Physicist in Medicine(AAPM).